The Relationship between Life Course Socioeconomic Conditions and Objective and Subjective Memory in Older Age - Morgane Künzi; Emilie Joly-Burra; Sascha Zuber; Maximilian Haas; Doriana Tinello; Chloé Da Silva Coelho; Alexandra Hering; Andreas Ihle; Gianvito Laera; Greta Mikneviciute; Silvia Stringhini; Bogdan Draganski; et al. (Brain Sciences, 2021)
While objective memory performance in older adults was primarily shown to be affected by education as indicator of life course socioeconomic conditions, other life course socioeconomic conditions seem to relate to subjective memory complaints. However, studies differ in which life course stages were investigated. Moreover, studies have explored these effects in an isolated way, but have not yet investigated their unique effect when considering several stages of the life course simultaneously. This study, therefore, examined the respective influence of socioeconomic conditions from childhood up to late-life on prospective memory (PM) performance as an objective indicator of everyday memory as well as on subjective memory complaints (SMC) in older age using structural equation modeling. Data came from two waves of the Vivre-Leben-Vivere aging study (<semantics>n=993</semantics>, <semantics>Mage=80.56</semantics>). The results indicate that only socioeconomic conditions in adulthood significantly predicted late-life PM performance. PM performance was also predicted by age and self-rated health. In contrast, SMC in older age were not predicted by socioeconomic conditions at any stage of the life course but were predicted by level of depression. In line with the cognitive reserve hypothesis, present results highlight the significance of education and occupation (adulthood socioeconomic conditions) for cognitive functioning in later life.